Principles of anatomy and physiology : an Indian adaptation - Gerard J Tortora; Derrickson, Bryan H (New Delhi Wiley, 2024)
Principles of Anatomy and Physiology has been recognized for its pioneering homeostac approach to learning the structure and funcon of the human body. It raises the standard for excellence in the discipline with its enhanced illustraon program, refined narrave, and dynamic resources. It has been designed to movate and support learners at every level, from novice to expert, and equip them with the skills they need to succeed in this class and beyond.
Keywords: Human physiology